Anthracnose on alfalfa caused by Colletotrichum americae-borealis in Córdoba province, Argentina - Bernanrdi Lima, Nelson; Conforto, Erica Cinthia; Serri, Dannae Lilia; Campilongo Mancilla, Ernesto Javier; Stenglein, Sebastian; Vargas Gil, Silvina (Elsevier, 2021)
Alfalfa is an important forage crop in Argentina, with a large area dedicated to its cultivation. However, plant diseases are a common cause of loss because they limit productivity and reduce forage quality. Anthracnose, caused by the Colletotrichum species, is one of the most important diseases affecting alfalfa worldwide. In July 2018, alfalfa plants with anthracnose symptoms were collected in commercial fields of Cordoba province, Argentina. Initially, infected plants showed small, pale gray lesions on stems, which turned oval and developed irregular dark brown/black borders as they enlarged. Three fungal isolates were obtained from the necrotic tissues of stems and single-spore purified. Based on the morphology and multilocus phylogenetic analysis, combined sequences of the partial glyceraldehyde-3-phosphate dehydrogenase (GAPDH), histone H3 (HIS3) and actin (ACT) genes, the three isolates were identified as Colletotrichum americae-borealis. Pathogenicity testing showed these isolates were pathogenic to alfalfa and Koch's postulates were verified by re-isolating the pathogen.